Natural history of chronic hepatitis B virus infection in childhood and efficacy of interferon therapy. (July 2014) - Takano, Tomoko; Tajiri, Hitoshi; Etani, Yuri; Miyoshi, Yoko; Tanaka, Yasuhito; Brooks, Stephen
Abstract: Objectives. In short-term observations, interferon (IFN) therapy has been shown to be effective in producing both biochemical and virological responses in children with chronic hepatitis B virus (HBV) infection. However, in long-term follow up, no studies have shown a clear advantage of IFN therapy during childhood. We conducted a retrospective study on the sustained effect of IFN therapy among a Japanese pediatric population. Methods and subjects. A retrospective study was performed on 155 children with chronic HBV infection who were followed in two affiliated hospitals during the period from 1986 to 2013. Results. The 155 patients comprised 97 males and 58 female. Infection route was maternal transmission in 96/155 patients. HBV genotype was A in 17, B in 6, and C in 51 patients. IFN therapy was performed in 48 patients. One year after the completion of IFN therapy, normalization of alanine aminotransferase (ALT) and lower viral levels (<10 4 copies/ml) was observed in 43 and 29 patients, respectively. The sustained effects of IFN therapy were evaluated by comparison between 43 hepatitis B e-antigen (HBeAg)-positive patients treated with IFN and 67 patients with chronic hepatitis B observed without IFN therapy. A Cox's proportional hazard analysis showed a higher seroconversion rate in the IFN group than in the untreated group ( p = 0.003). Similarly, there were higher rates of ALT normalization and lower viral levels in the IFN group than in the untreated group ( p = 0.001 for both). Conclusion. IFN therapy showed sustained effects for achieving ALT normalization and HBeAg seroconversion and for reducing the viral load in children with chronic hepatitis B.